Meningkatkan Hasil Belajar Keperawatan Dasar Melalui Metode Pembelajaran Problem Base Learning (PBL) Mahasiswa Tingkat I Akper Bhakti Husada Cikarang Tahun 2018/2019 - Marlina, Lina; Nurdini, Rini (2020)
Background : Learning outcomes for basic nursing courses for two years at Akper Bhakti Husada Cikarang still do not meet the minimum graduation limit for TA. 2016/2017 as many as 13% of the total 59 students and for TA. 2017/2018 as many as 23% of 70 students, while the minimum target for graduation is 80%. So we need an effective learning method that can improve student learning outcomes in basic nursing courses. Problem Based Learning (PBL) we can say as a learning model that prepares students to think critically and analytically, and seeks and uses appropriate learning resources to deal with an existing problem. The tutorial (tutoring) is academic assistance or tutoring by tutor to students (tutee) to help smooth the independent learning process of individual students or groups related to teaching material Method : This research is a classroom action research in the form of a descriptive level for first-level students for basic nursing courses. Results : The average value of the process scores for students scenario 1, 2 and 3 have exceeded the value of the graduation limit or expected value. Pre-test scores for each scenario have not reached the expected value, still below 68. The average post-test scores of students have been more than the expected value. Conclusion : Tutorial methods can improve their ability to create alternatives and solve problems. It is recommended that the tutorial method can be applied to other subjects besides basic nursing. The selection of respondents / students studied must be chosen that has a level of intelligence or ability that is not much different.